(untitled) (Research, Society and Development, 2021)
Introduction: Food is part of the set of “Social Rights” provided for in the Federal Constitution of 1988, and its guarantee is a duty of the State. The National School Feeding Program (PNAE) fulfills the State’s duty with education in this matter of food. Due to the COVID-19 pandemic situation, normative acts were published altering the PNAE legislation, of an exceptional nature as long as the public calamity lasts, in order to continue implementing the policy and offering the right to food to students. Methodology: A literature review study. Objective: This work seeks to present and discuss the PNAE public policy in its historical context and in times of pandemic. Results and discussion: An exposition of the historical context of policy construction and its implementation situation during this pandemic period. Conclusion: The elaboration of this review can contribute to the understanding of the policy and highlight its importance in the educational and social context of the country.